PROSES BERPIKIR SISWA DALAM MENYELESAIKAN SOAL BERPIKIR TINGKAT TINGGI MATERI BANGUN DATAR SELAMA PEMBELAJARAN KOLABORATIF DI MTs SATU ATAP SILO - Apriwiyani, Hesti; Sunardi, S; Setiawan, Toto’ Bara (Kadikma, 2018)
Abstract The purpose of this study is to describe the thinking process of students in solving the problem of high-level thinking in accordance with predetermined indicators. The high-level thinking problem in this study refers to taxonomy bloom ie C4 (analysis), C5 (evaluation), and C6 (creation). Collaborative learning to enhance students' active role in solving high-order thinking problems. The thinking process of students in geometry in this study can be described based on van Hiele's theory. This research is a descriptive research with qualitative approach. Result of research from 23 students through collaborative learning, got 2 students according to van Hiele thinking level. The data obtained are 1 students who are in the process of thinking level 1 (analysis) and 1 student is in the process of thinking level 2 (informal deduction). Keywords: The Process of thinking, collaborative learning, van Hiele theory